Clinical prototype of pigment and flow imaging optical coherence tomography for posterior eye investigation - Makita, Shuichi (Biomed Opt Express, 2018)
Measurements of the randomness of polarization (RP) obtained using polarization-sensitive optical coherence tomography (PS-OCT) are applied in several applications, and RP is attractive for posterior eye imaging. The addition of RP without retardation requires a minimal extension to standard OCT; therefore, we developed a prototype OCT system with a simplified scheme for RP measurement. A compact polarization-diversity receiver module is the only required hardware extension to a standard OCT system. All components were packed into the retinal scanning head. The degree-of-polarization uniformity and complex-decorrelation based OCT angiography were calculated using noise-corrected algorithms that accounted for the depth-dependent noise power. The structure, melanin, and blood flow distribution imaging of in vivo human eyes were demonstrated. Pathological eye imaging shows potential applications for combinations of these contrasts.